Validation of chromogenic in situ hybridization reactions for DNA and RNA detection in formalin-fixed paraffin-embedded tissue - Raquel L. Monteiro; Daniela S. Damaceno; Lidia M. Kimura; Cinthya S. Cirqueira; Juliana M. Guerra; Leonardo José T. Araújo (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Introduction: Chromogenic in situ hybridization (CISH) is used alternatively to the traditional immunohistochemical methods for the diagnosis of infectious diseases in formalin-fixed paraffin-embedded samples, since it presents high sensitivity and specificity. This type of sample undergoes several chemical modifications during histological processing, and both poor and excessive fixation can impair sample quality, making it difficult to obtain good results. In CISH, it is common to use positive samples as quality control for the reactions; however, this practice does not provide any information regarding the preservation of the genetic material, nor does it avoid false-negative results. Objective: The objective of this study was to validate the deoxyribonucleic acid (DNA) (+) and (-), and ribonucleic acid (RNA) (+) and (-) control probes to be used as quality control for the samples, evaluating preservation of the genetic material. Materials and methods: Twelve histological sections were used (in quadruplicate, n = 48), prepared from a pool of tissues without microscopic changes related to infectious and/or inflammatory processes. The CISH protocol was conducted according to the manufacturer's instructions, standardized under the conditions of our laboratory, using commercial DNA and RNA probes chemically linked to digoxigenin. Results and conclusion: Our results were very satisfactory, showing high reproducibility, accuracy, sensitivity and analytical specificity, high predictive values for positive and negative assays and with zero ratio of false-positive and false-negative results, allowing the validation of this reaction.